(untitled) (Italian Journal of Public Health, 2008)
Background: Genomic DNA patterns generated by pulsed-field gel electrophoresis (PGFE) are highly specific for different strains of an organism and have significant value in epidemiologic investigations of infectious disease outbreaks. A disadvantage of PFGE is that the procedure requires up to 6 days to complete. Methods: We developed a rapid PFGE protocol for subtyping Legionella pneumophila isolates based on the standardized protocol currently used. Various combinations of reaction conditions (e.g., lysis time and temperature, restriction enzyme concentration) and electrophoresis parameters were applied to devise a simple and rapid PFGE protocol that could also be used for frozen bacteria. Results: PFGE analysis of Legionella pneumophila isolates can be completed in 26 hours using this protocol compared to 6 days for the conventional one. Conclusions: We successfully applied a rapid PFGE protocol for Legionella pneumophila typing and comparison of the patterns obtained from the rapid compared with the conventional method showed that the rapid protocol gave identical and highly reproducible results.